Assessment of the microbial contamination in “Do It Yourself” (DIY) stores - Dias, Marta (2024)
Funding Information: The author(s) declare that financial support was received for the research, authorship, and/or publication of this article. This project was supported by FCT/MCTES UIDP/05608/2020 (https://doi.org/10.54499/UIDP/05608/2020) and UIDB/05608/2020 (https://doi.org/10.54499/UIDB/05608/2020). This work is also supported by national funds through FCT/MCTES/FSE/UE, 2023.01366.BD; UI/BD/153746/2022 and CE3C unit UIDB/00329/2020 (https://doi.org/10.54499/UIDB/00329/2020); UI/BD/151431/2021 (https://doi.org/10.54499/UI/BD/151431/2021); and Instituto Polit\u00E9cnico de Lisboa, Lisbon, Portugal for funding the Projects IPL/IDI&CA2024/WWTPSValor_ESTeSL and IPL/IDI&CA2024/MycoSOS_ESTeSL. Publisher Copyright: Copyright © 2024 Dias, Gomes, Pena, Cervantes, Gonçalves, Carolino, Twarużek, Kosicki, Ałtyn, Caetano, Viegas and Viegas.